2013
DOI: 10.1111/jcpt.12079
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes associated with a thrice-weekly antimicrobial stewardship programme in a 253-bed community hospital

Abstract: A thrice-weekly, pharmacist-driven ASP can decrease antimicrobial expenditure, shorten duration of therapy and decrease the utilization of carbapenems, vancomycin and levofloxacin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 10 publications
1
27
0
5
Order By: Relevance
“…57,671 Collectively, their active stewardship of antibiotic prescribing is acknowledged to limit overprescribing 672 and improve adherence to guidelines. [673][674][675][676] However, their oversight of surgical prophylaxis is constrained by the charting and timing of the administration of such drugs within the theatre environment. [677][678][679] There are many other ways in which patients may acquire infections while in hospital.…”
Section: Reducing Health-care-associated Infectionmentioning
confidence: 99%
“…57,671 Collectively, their active stewardship of antibiotic prescribing is acknowledged to limit overprescribing 672 and improve adherence to guidelines. [673][674][675][676] However, their oversight of surgical prophylaxis is constrained by the charting and timing of the administration of such drugs within the theatre environment. [677][678][679] There are many other ways in which patients may acquire infections while in hospital.…”
Section: Reducing Health-care-associated Infectionmentioning
confidence: 99%
“…Although a few integrative data sources were described [5,6], most were not developed and individualized for antimicrobial stewardship purposes. Studies that provided mention of ASP specific systems or databases [7][8][9][10][11][12][13][14] generally offered little description of their capacity for ASP evaluation and research.…”
Section: Data Sourcesmentioning
confidence: 99%
“…This tool was used to identify the levels of evidence for the publications included in this review. About half of the included studies (29/58) employed a before-and-after study design [6, 7, 9-11, 13, 14, 17-38], and 62 % (36/ 58) constituted level IV evidence [6,7,[9][10][11][12][13][14]. During the review period, there were no level I publications (systematic reviews of randomized controlled trials (RCTs)), and we identified only five (9 %) published RCTs (level II) [45, 46, 47•, 48, 49].…”
Section: Study Design Study Design and Hierarchy Of Evidencementioning
confidence: 99%
See 2 more Smart Citations